Reducing child undernutrition: Past drivers and priorities for the post-MDG era - Smith, Lisa C.; Haddad, Lawrence James (Elsevier, 2015)
As the post-MDG era approaches in 2016, reducing child undernutrition is gaining high priority on the international development agenda, both as a maker and marker of development. Revisiting Smith and Haddad (2000), we use data from 1970 to 2012 for 116 countries, finding that safe water access, sanitation, women’s education, gender equality, and the quantity and quality of food available in countries have been key drivers of past reductions in stunting. Income growth and governance played essential facilitating roles. Complementary to nutrition-specific and nutrition-sensitive programs and policies, accelerating reductions in undernutrition in the future will require increased investment in these priority areas.